2005
DOI: 10.1152/ajpregu.00341.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis stimulates calpain activity in skeletal muscle by decreasing calpastatin activity but does not activate caspase-3

Abstract: , and Per-Olof Hasselgren. Sepsis stimulates calpain activity in skeletal muscle by decreasing calpastatin activity but does not activate caspase-3. Am J Physiol Regul Integr Comp Physiol 288: R580 -R590, 2005. First published November 24, 2004 doi:10.1152/ajpregu.00341.2004.-We examined the influence of sepsis on the expression and activity of the calpain and caspase systems in skeletal muscle. Sepsis was induced in rats by cecal ligation and puncture (CLP). Control rats were sham operated. Calpain activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 50 publications
10
87
2
1
Order By: Relevance
“…Sorimachi et al and Enns et al both found that ischemia/reperfusion results in a decline in calpastatin inhibitory activity with no change in fluorometrically determined calpain activity [39,40], but that calpain inhibition improves post-ischemic contractile function. Wei et al found altered calpain activity due to a change in calpastatin inhibitory activity in a model of sepsis-mediated muscle proteolysis [41]. Shi et al found down regulation of the 41 kDa isoform of calpastatin in kidney following renal ischemia/reperfusion similar to what we observed in the RV [42].…”
Section: Discussionsupporting
confidence: 83%
“…Sorimachi et al and Enns et al both found that ischemia/reperfusion results in a decline in calpastatin inhibitory activity with no change in fluorometrically determined calpain activity [39,40], but that calpain inhibition improves post-ischemic contractile function. Wei et al found altered calpain activity due to a change in calpastatin inhibitory activity in a model of sepsis-mediated muscle proteolysis [41]. Shi et al found down regulation of the 41 kDa isoform of calpastatin in kidney following renal ischemia/reperfusion similar to what we observed in the RV [42].…”
Section: Discussionsupporting
confidence: 83%
“…However, measuring caspase-3 activity in muscle samples is not useful as a diagnostic method because we and others have found that caspase-3 activity in muscle samples is low and the "signal to noise" ratio is high even in muscles of rodents with demonstrably high rates of protein degradation. Wei et al (21) reported difficulty in detecting changes in caspase-3 activity in muscle of septic rats. Sepsis activates the UPP in muscle, so their results might be related to degradation of caspase-3 by the ATP-dependent UPP (22).…”
Section: Discussionmentioning
confidence: 99%
“…Calpains are calcium-dependent cysteine proteases that have been suggested to play roles in several disorders, especially muscular dystrophy. Evidence for calpain's activation has been reported in muscles of animals with sepsis (95). Although inhibition of the calcium-activated proteases in muscles from rodents with uremia or several other types of atrophy has not been found to block the increase in protein degradation or the degradation of myofibrillar proteins or the accumulation of the 14-kD actin fragment in muscle cells (92), the transgenic expression of calpastatin, an endogenous calpain inhibitor, can reduce denervation atrophy and progression of muscular dystrophy in mice (96).…”
Section: Initial Cleavage Of Myofibrillar Proteins In Uremia By Caspamentioning
confidence: 99%